2017
DOI: 10.17645/up.v2i4.1039
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Green Infrastructure in a Philadelphia Neighborhood

Abstract: While the Philadelphia Water Department (PWD) is counting on Green Stormwater Infrastructure (GI) as a key component of its long-term plan for reducing combined sewer overflows, many community stakeholders are also hoping that investment in greening can help meet other ancillary goals, collectively referred to as sustainable redevelopment. This study investigates the challenges associated with implementation of GI in Point Breeze, a residential neighborhood of South Philadelphia. The project team performed a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Many of these residents have witnessed significant growth and change from urban intensification that has taken place in both cities over the last several In their willingness to consider investing in lot-level stormwater management actions such as planting trees, reducing hard surfaces or installing backwater valves to strengthen flood resilience within their own home sites, many of these residents embrace -within limits -the role of self-governing citizen within a neoliberal model of climate change governance, if financial incentives and guidance are made available by governments. This result corresponds with findings from other empirical research on resident responses to suggested home site stormwater and flood management practices (Lim, 2018;Thistlethwaite et al, 2017;Zidar et al, 2017), and reflects the influence of continuing trends among North American municipalities over the last several decades toward allocating greater shares of responsibility to individual citizens in dealing with common environmental issues and risk.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Many of these residents have witnessed significant growth and change from urban intensification that has taken place in both cities over the last several In their willingness to consider investing in lot-level stormwater management actions such as planting trees, reducing hard surfaces or installing backwater valves to strengthen flood resilience within their own home sites, many of these residents embrace -within limits -the role of self-governing citizen within a neoliberal model of climate change governance, if financial incentives and guidance are made available by governments. This result corresponds with findings from other empirical research on resident responses to suggested home site stormwater and flood management practices (Lim, 2018;Thistlethwaite et al, 2017;Zidar et al, 2017), and reflects the influence of continuing trends among North American municipalities over the last several decades toward allocating greater shares of responsibility to individual citizens in dealing with common environmental issues and risk.…”
Section: Discussionsupporting
confidence: 88%
“…This conceptualization also involves consideration of how nature is reproduced in cities through human activity, and how built structures may accommodate ecological needs and flows (Braun, 2005;Francis et al, 2012). 54 The academic literature has emphasized a crucial requirement for community support in implementing ecosystem-based adaptation policy in cities, as well as a need to better understand citizen responses to related suggested practices within the home site space (Derkzen et al, 2017;Zidar et al, 2017). Through their preferred approaches to home site landscaping (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, pressures need to be taken up and translated by actor agency [29,[44][45][46]. Considering these views, context adaptability varies both between countries and within them, e.g., in Onondaga County Metropolitan and the city of Philadelphia [102,103]. Based on only the reviewed articles, all of the adaptability elements on context and capacity (including human agency) are found in Philadelphia, which, according to [103], is the first city in the US to attempt an entirely green approach to meeting federal regulations, and was subsequently recognized as a leader in transitioning to SUWM.…”
Section: Context and Instrumentsmentioning
confidence: 99%